Compensated Intensity-Modulated Optical Fibre Bending Sensor based on Tilt Angle Loss Measurement - Mohd Anwar, Zawawi; S. O., Keeffe; E., Lewis (2014)
This paper presents the implementation of an extrinsic optical fibre sensor based on intensity modulation technique aimed for continuous bending assessment of human spine movement. The sensor under investigation is non-invasive and capable of providing a continuous measurement of the bending angle in both flexion and extension directions of the human spine. The bending assessment is determined based on the measurement of the tilt angle loss between an input fibre and dual output fibres. Additionally, a reference fibre is also integrated into the sensor configuration by means of the divided beam system to compensate for any output variation resulting from temperature changes.